Expans\~ao de área agrícola no piauí do matopiba - Rogério Edivaldo Freitas (Instituto de Pesquisa Econômica Aplicada (IPEA), 2025)
The goal of this study was to measure and map the agricultural expansion areas for temporary and permanent crops from 1995 to 2022 at the Piauí's County level concerning the Matopiba space. Data from IBGE were employed, and the study is based on the Embrapa's technical note (Miranda, Magalh\~aes e Carvalho, 2014). The methodological approach encompasses three quantitative stages. The results highlight 17 among the 33 evaluated counties. They are the most relevant in the Piaui's and Brazil's agricultural expansion process. They present a proportionally high contribution to the increase of the Brazilian farm area, and the more dynamic process is related to the temporary crops, especially the duo soybean-corn. In the context of the permanent crops, results highlight the areas dedicated to banana and cashew nut.
Keywords: Q10; Q15; 330; Piauí; Matopiba; agriculture; Brazil